Electrophysiological parameters and anatomical evaluation of left bundle branch pacing in an in vivo canine model. (18th December 2019) - Chen, Xueying; Jin, Qinchun; Li, Bingyu; Jia, Jianguo; Sharma, Parikshit S.; Huang, Weijian; Su, Yangang; Ge, Junbo
Abstract: Introduction: Left bundle branch pacing (LBBP), a form of conduction system pacing in addition to His bundle pacing (HBP), can potentially maintain left ventricular electrical synchrony with better sensing and a low and stable capture threshold. Methods: We performed both HBP and LBBP using a canine model (n = 3; male; weight 30‐40 kg). The electrocardiogram (ECG), intracardiac electrogram characteristics, and pacing parameters were compared between HBP and LBBP. The hearts were isolated and stained by Lugol's iodine (5%) to assess the relative locations of the leads in relation to the conduction system. Results: The average potential to ventricle interval was longer with HBP compared to LBBP (26.67 ± 3.06 ms vs 12.67 ± 1.15 ms; P  = .002). There were also notable differences in the pacing parameters between HBP and LBBP: R‐wave amplitude (2.67 ± 0.42 mV vs 11.33 ± 3.06 mV; P  = .008), pacing impedance (423.3 ± 40.4 vs 660.0 ± 45.8; P  = .003), and threshold (2.30 ± 0.66 V/0.4ms vs 0.67 ± 0.15 V/0.4 ms; P  = .014). The paced morphology of ECG was similar to the intrinsic with HBP while a right bundle branch block pattern was noted with LBBP. The anatomical evaluation revealed the location of the leads and the average lead depth was significantly more with LBBP as compared to HBP (12.33 ± 1.53 mm vs1.83 ± 0.29 mm; P  < .0001). Furthermore, with LBBP, the tip of the lead helix was noted to be around the LBB. Conclusion: This in vivo canine model study confirms the significant differences between HBP and LBBP. Furthermore, this model provides a precise anatomic evaluation of the location and the depth of the leads in relation to the conduction system.